A Coursebook principles of English language teaching = - Nguyễn, Văn Lợi (Nxb. Đại học Cần Thơ, 2017)
Nội dung sách gồm: chapter 1 introduction to teaching and learning ; chapter 2 views of language and english as an international language; chapter 3 theories of learning and second language learning ; chapter 4 learner factors ; chapter 5 contextual factors ; chapter 6 ;rinciples of teaching english as an international language .